Moral Character and Responsibilityfor Semende Peoplein Ulu Danau, South Sumatera - Setiawan, Hatta; Darmawan, Cecep (Bina Nusantara University, 2016)
This research was aimed to know the values being implemented in the community to maintain the existence of the custom in Ulu Danau village in South of Sumatera province. The method applied was ethnography with a qualitative approach. Then, the data were collected by observtion, which would be analyzed and concluded. The results of the analysis and discussion show that Semende people in the village of Ulu Danau see the custom of Tunggu Tubang and Jenang Jurai as normal things to create the responsible character, and moral character that will be embodied in the implementation of Besundi, Besindat, and Besingkuh. The value of responsibility on Tunggu Tubang custom teaches the value of hard work, the message, honesty, and discipline. As for custom of Jenang Jurai, it is shown through the value of independence, democracy, fairness, and tolerance. Besundi Besindat Besingkuh show the values of mannerism and deportment. Last, it is seen as efforts by the people in the community to maintain the custom by giving the space and an emphasis on it.